Does sex impact neuropsychiatric symptom burden in APOε4 carriers with at‐risk cognitive conditions?: Developing topics. (7th December 2020) - Dissanayake, Andrew S; Bowie, Christopher R; Butters, Meryl A; Flint, Alastair; Gallagher, Damien; Golas, Angela C; Herrmann, Nathan; Kennedy, James L; Kumar, Sanjeev; Lanctot, Krista L; Mah, Linda; Mulsant, Benoit H; et al.
Abstract: Background: The Apolipoprotein E (APOE) ε4 allele is a well‐established genetic risk factor of Alzheimer's disease (AD). While sex may play an important modulatory role in the association between APOε4 and certain neuropsychiatric symptoms (NPS) in AD 1, it is unclear whether or not this risk extends to cognitively at‐risk populations with Mild Cognitive Impairment (MCI) or a history of Major Depressive Disorder (MDD). This cross‐sectional analysis compared NPS burden between males and females in a cohort of APOε4 carriers with at‐risk cognitive conditions of AD. Method: We analyzed the Neuropsychiatric Inventory Questionnaire (NPI‐Q) data of 51 symptomatic APOε4 carriers (age = 71.9 ± 5.2) from the PACt‐MD cohort which was comprised of older persons from three at‐risk groups of AD: MCI; MDD without MCI; and MDD with MCI. We stratified participants by sex to compare their NPS severity. We tested whether there was a significant association between sex and i) NPI‐Q total score, and ii) NPI‐Q severity score. We chose not to stratify by zygosity or diagnosis due to the sample size. Result: Female APOε4 carriers ( n = 33, MNPI Total = 2.27, MNPI Severity = 3.55 ) had significantly higher NPI‐Q total scores(t = 2.15, df = 43.67, p = 0.037, d = 0.50) and significantly higher NPI‐Q severity scores (t = 2.06, df = 45.37, p = 0.044, d = 0.48) than male carriers ( n = 18, MNPI Total = 1.72, MNPI Severity = 2.44). There were no significant differences in the prevalence of certain NPS between male and female carriers. Conclusion: Our findings support the need to further investigate whether sex influences the effect of APOε4 on NPS burden. Although female carriers showed significantly higher levels of NPS burden, aligning with previous findings 1, our analysis was limited by the small number of symptomatic male carriers (n = 18). Thus, further studies with larger samples are needed to elucidate the interaction between sex and APOε4 status on NPS burden. References: Kim, J., Fischer, C. E., Schweizer, T. A., & Munoz, D. G. (2017). Gender and Pathology‐ Specific Effect of Apolipoprotein E Genotype on Psychosis in Alzheimer's Disease. Current Alzheimer research, 8, 834–840.